THE COMBINATION OF KARTAGENER SYNDROME WITH FOCAL SEGMENTAL GLOMERULOSCLEROSIS: CASE REPORT - Burdeina, E.V.; Nepomnyashchy, V.N.; Kolesnyk, N.A. (Ukrainian Journal of Nephrology and Dialysis, 2015)
Kartagener syndrome - a form ofprimary ciliary dyskinesia, which combines situs inversus totalis or only dextrocardia with the defeat of the respiratory system. The combination of glomerulonephritis with Kartagener syndrome is rare, and that was the reason for describing a patient with Kartagener syndrome and focal - segmental glomerulosclerosis observed in clinic.